Improved Wavelet Reassigned Scalograms and Application for Modal Parameter Estimation. (2011) - Peng, Z.K.; Meng, G.; Chu, F. L.
Abstract : The present work carries out a comprehensive investigation into the border distortion deficiency for the conventional scalogram and the reassigned scalogram. The reasons for this deficiency are analyzed, and a simple way is suggested to determine the border distortion ranges. New methods are proposed to reduce the border distortions in both the scalograms. The practical meanings of the border distortion improvement method are demonstrated by applying both the scalograms with and without border distortion improvements to estimate the modal parameters for a 2-DOF linear system. The estimation results indicate that, in the presence of noise, which is inevitable in practice, for the mode with weak amplitude, the reassigned scalogram can perform better than the conventional scalogram in estimating the modal parameters. In addition, for the mode with short effective duration, its frequency components at the border distortion ranges are of great importance for the modal parameter estimation purpose, and the border distortion improvement method can greatly increase the estimation accuracy.